Alzheimer’s Disease, Neuroprotection, and CNS Immunosenescence - Streit, Wolfgang J.; Xue, QingShan (Frontiers in Pharmacology, 2012)
This review is focused on discussing in some detail possible neuroprotective functions of microglial cells. We strive to explain how loss of these essential microglial functions might contribute towards the development of characteristic neuropathological features that characterize Alzheimer’s disease. The conceptual framework guiding our thinking is provided by the hypothesis that microglial senescence accounts for impaired neuronal protection and consequent neurodegeneration.